2019
DOI: 10.1136/openhrt-2018-000937
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of cardiac resynchronisation therapy in patients with heart failure with atrial fibrillation: a systematic review and meta-analysis of observational studies

Abstract: BackgroundCardiac resynchronisation therapy (CRT) is beneficial in selected patients with heart failure (HF) in normal sinus rhythm (NSR). We sought to evaluate the impact of CRT with or without atrioventricular junction (AVJ) ablation in patients with HF with concomitant atrial fibrillation (AF)Methods and resultsLiterature was searched (inception through 30 August 2017) for observational studies that reported outcomes in patients with HF with CRT and AF that reported all-cause and cardiovascular mortality. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 68 publications
1
33
0
Order By: Relevance
“…Interestingly, the type of AF was not associated with the prediction of composite endpoint of HF patients, possibly due to benefits from optimal drug treatments after discharge and a high percentage of biventricular pacing (BIVP, median > = 98%), which was consistent with previous conclusions [15,32]. Even though much data have recommended AVJA for patients undergoing CRT in persistent or permanent AF to ensure better BIVP and prognosis, few studies have explored the effects of paroxysmal AF on long-term prognosis [11]. One study indicated that paroxysmal AF increased the risk of mortality by 32% after adjustment for age, sex, BIVP% and shock treatment of CRT-D compared with 51 and 28% in persistent and permanent AF, respectively [32].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Interestingly, the type of AF was not associated with the prediction of composite endpoint of HF patients, possibly due to benefits from optimal drug treatments after discharge and a high percentage of biventricular pacing (BIVP, median > = 98%), which was consistent with previous conclusions [15,32]. Even though much data have recommended AVJA for patients undergoing CRT in persistent or permanent AF to ensure better BIVP and prognosis, few studies have explored the effects of paroxysmal AF on long-term prognosis [11]. One study indicated that paroxysmal AF increased the risk of mortality by 32% after adjustment for age, sex, BIVP% and shock treatment of CRT-D compared with 51 and 28% in persistent and permanent AF, respectively [32].…”
Section: Discussionsupporting
confidence: 82%
“…However, the efficacy of CRT in patients with atrial fibrillation (AF) still remains a knowledge gap, although the concurrence of AF and HF is common in clinical practice, ranging from < 5% in asymptomatic HF patients to nearly 50% in symptomatic HF patients [4]. Several studies have supported the benefits of CRT in AF patients [5][6][7][8], though compared with those in sinus rhythm, AF was also associated with a higher risk of mortality in CRT candidates [9][10][11]. Unfortunately, there are currently no predictive models proposed in clinical practice for AF patients undergoing CRT that can stratify patients by risk and evaluate their long-term prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Atrioventricular junction ablation is performed in patients with symptomatic, drug‐refractory, long‐standing persistent AF as part of an ‘ablate and pace’ strategy 6 . The APAF‐CRT and other studies have demonstrated that BVP combined with AVJ ablation can be the mainstay of pacing and ablation therapy in patients who have decreased ejection fraction or clinical heart failure by reducing the negative haemodynamic effects of right ventricular apical pacing and underlying rapid AF 15,16 . The benefits of BVP are limited by non‐responders and patients with suboptimal clinical outcomes, which may in part be due to the fact that BVP does not completely reverse electrical dyssynchrony, but rather decreases its magnitude, limiting its application, especially in patients with narrow QRS duration or non‐LBBB 5 .…”
Section: Discussionmentioning
confidence: 99%
“…A more recent meta-analysis of observational studies, which included 83,571 patients, also demonstrated a significantly higher mortality rate after CRT implant in patients with AF, compared to those in sinus rhythm. 9 In addition, patients with heart failure and AF were not found to have a significant reduction in mortality or in a composite endpoint of mortality or heart failure hospitalization after CRT, when compared to either ICD or medical therapy. Importantly, in the sub-group of patients with AF who received an AV node ablation, mortality was significantly lower, and equivalent to patients with sinus rhythm, as discussed later in this article.…”
Section: The Evidence For Cardiac Resynchronization Therapy In Patients With Atrial Fibrillationmentioning
confidence: 93%
“…6,7 AF appears to attenuate the response to CRT, and patients with AF have a higher longterm mortality after CRT implant compared to those in sinus rhythm. 8,9 The delivery of CRT may also alter the natural progression of AF in patients with heart failure. In this article we review the evidence for CRT in patient with AF, explore the relationship between AF and CRT delivery, and discuss the treatment options available in this patient cohort.…”
Section: Introductionmentioning
confidence: 99%